Interpersonal communication patterns of facilitators for child victims of sexual violence in Aceh Province - Salami, Salami; Akmal, Saiful; Herawati, Herawati (Universitas Islam Negeri Ar-Raniry, 2023)
Cases of sexual violence against children in Aceh are increasingly worrying. The data collected from SIMFONI-PPA of the Ministry of Women’s Empowerment and Child Protection recorded that in 2021 there were 5,463 cases of violence against children nationally. The impacts felt by the victims of sexual violence who needed psychological assistance included hatred, revenge, rebellion, and trauma. This study, therefore, aimed to investigate the communication patterns used by the facilitators at the Protection of Women and Children of Aceh Province in handling child victims of sexual violence and the obstacles faced in the assistance process. By using a qualitative and phenomenological approach, the study collected the data through in-depth interviews and documentation. The researcher interviewed two lawyers, two counsellors, and one psychologist. At the same time, documentation data was acquired from records and relevant documents in the UPTD PPA Aceh office. The results of the study revealed that there were two patterns of communication used by the facilitators of UPTD. Psychologists and counsellors used primary communication patterns through verbal and non-verbal communication simultaneously. On the other hand, lawyers used a circular communication pattern by having more communication with the victims’ families. Moreover, the obstacles experienced by the facilitators included requiring extra approaches and assistance for child victims with special needs. Other obstacles include frequent threats and terror, the dysfunction of the safe house for victims who needed temporary shelter, and the unavailability of a special treatment section or room in the hospital for victims of sexual violence.